Spotlight on graduate student, Azhar Fakharuddin, PhD (Advanced Materials - M. M., Yusoff; Saifful Kamaluddin, Muzakir; Chin, Mei Lee; Siti Aisah, Harun; Norhayati, Nordin; Ezrinda, Mohd Zahidee; Mohd Fazli, Farida Asras; Nurul Nadia, Abd Razak (Penerbit UMP, 2011)
A?har Fakharuddin originates from Azad Kashmir, Pakistan. He has Bachelor and Masters degrees in electronic engineering. The decision to change to science and technology field was one of the most difficult decisions he has ever made.